2017
DOI: 10.1007/s10334-017-0650-z
|View full text |Cite
|
Sign up to set email alerts
|

Automated reference-free detection of motion artifacts in magnetic resonance images

Abstract: Automated detection of motion artifacts in MRI is feasible with good accuracy in the head and abdomen. The proposed method provides quantification and localization of artifacts as well as a visualization of the learned content. It may be extended to other anatomic areas and used for quality assurance of MR images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 29 publications
3
66
0
Order By: Relevance
“…In contrast, DL uses multiresolution image features learned from the image data. The high performance achieved using our model supports the emerging role of DL in image quality assessment as reported in recent studies for automated detection of motion artifacts in head and abdomen MRI, 14 automated image quality evaluation of T 2 -weighted liver MRI, 15 and detection of motion artifacts in brain MRI 16 (Table 3).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, DL uses multiresolution image features learned from the image data. The high performance achieved using our model supports the emerging role of DL in image quality assessment as reported in recent studies for automated detection of motion artifacts in head and abdomen MRI, 14 automated image quality evaluation of T 2 -weighted liver MRI, 15 and detection of motion artifacts in brain MRI 16 (Table 3).…”
Section: Discussionsupporting
confidence: 82%
“…The major advantage of DCNNs is their ability to self‐learn the image features that in traditional algorithms are hand‐engineered . Recent studies have demonstrated the feasibility of DCNNs for automated assessment of image quality of MR images acquired from a single site . It is unclear whether the results can be successfully generalized to multicenter datasets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning methods has also been applied to MR artifact detection, e.g. poor quality spectra in MRSI [188]; detection and removal of ghosting artifacts in MR spectroscopy [189]; and automated reference-free detection of patient motion artifacts in MRI [190].…”
Section: Image Restoration (Denoising Artifact Detection)mentioning
confidence: 99%
“…Their algorithm used training data from fruit images and artificial motion data. Also, Kustner et al [6] proposed a patch-based motion artefact detection method for brain and abdomen MR images, but they made their tests on a small dataset of 16 MR images with significant motion artefacts. Motion artefacts in CMR imaging are largely caused by ECG mistriggering and pose a significantly different problem.…”
Section: Introductionmentioning
confidence: 99%